2022
DOI: 10.1016/j.jsxm.2022.05.100
|View full text |Cite
|
Sign up to set email alerts
|

Clitoral Phimosis Should Have its own Diagnostic and Procedural Codes

Abstract: Introduction Clitoral phimosis occurs when the prepuce adheres to the glans clitoris. Similarly, penile phimosis occurs when the prepuce adheres to the glans penis. Symptoms of clitoral phimosis can include pain, difficulty with arousal, and muted or absent orgasm. While previous studies on the prevalence of clitoral phimosis in a group of 589 college students in a health clinic was 33%, and in a population of 614 patients with sexual dysfunction, it was 23%. There are no diagnosis codes (ICD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gender dysphoria, genitourinary syndrome of menopause (GSM), interstitial cystitis (IC), pelvic pain, persistent genital arousal disorder (PGAD), persistent orgasm illness syndrome (POIS) and balanitis secondary to clitoral phimosis are just a few of the diagnoses underrepresented in urology research and training -all of which may contribute to sexual dysfunction in patients and may compromise patient outcomes. [7][8][9][10] Other studies have suggested that urology residency does not pay su cient attention to sexual communication skills and dysfunction, speci cally in the context of treating prostate cancer treatmentrelated sexual dysfunction. 11,12 Krouwel et al surveyed 87 urology residents in the Netherlands and found the majority did not feel competent to adequately advise about treatment of sexual dysfunction in patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Gender dysphoria, genitourinary syndrome of menopause (GSM), interstitial cystitis (IC), pelvic pain, persistent genital arousal disorder (PGAD), persistent orgasm illness syndrome (POIS) and balanitis secondary to clitoral phimosis are just a few of the diagnoses underrepresented in urology research and training -all of which may contribute to sexual dysfunction in patients and may compromise patient outcomes. [7][8][9][10] Other studies have suggested that urology residency does not pay su cient attention to sexual communication skills and dysfunction, speci cally in the context of treating prostate cancer treatmentrelated sexual dysfunction. 11,12 Krouwel et al surveyed 87 urology residents in the Netherlands and found the majority did not feel competent to adequately advise about treatment of sexual dysfunction in patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%